2020
DOI: 10.1111/cdoe.12576
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life course factors and oral health among young Norwegian adults

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…An easily available alternative is to use self-reported number of teeth, applied in questionnaires or interviews, and hence more suitable in larger epidemiological studies. Several studies have used self-reported measures to explore oral health status at group- or population level [ 10 12 ]. Knowing the validity and reliability of self-reported values is therefore crucial.…”
Section: Introductionmentioning
confidence: 99%
“…An easily available alternative is to use self-reported number of teeth, applied in questionnaires or interviews, and hence more suitable in larger epidemiological studies. Several studies have used self-reported measures to explore oral health status at group- or population level [ 10 12 ]. Knowing the validity and reliability of self-reported values is therefore crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Only one UK study performed a public preference survey that included the WTP of preschool children’s parents and found that parents’ valuation for dental caries prevention was higher if it concerned permanent teeth compared to primary teeth [ 13 ]. With the growing amount and quality of evidence for beneficial effects of starting oral health prevention early in life, preferably around first tooth eruption [ 14 , 15 , 16 ], it is interesting to investigate WTP and WTIT for primary prevention among parents of preschool children. Therefore, this study aims to explore the WTP and WTIT for primary prevention in parents of preschool children and to describe whether these are related to the parents’ demographic and socio-economic characteristics and behavioural attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Although we could not determine whether the patients were fearful or had BMP even before the restraint situation, negative experiences are a well-known aetiological cause for the development of DFA (Klingberg and Broberg 2007 ; Klingberg 2008 ; Locker et al 2001 ; Milsom et al 2003 ; Ost and Hugdahl 1985 ; Seligman et al 2017 ; Ten Berge et al 2002 ; Åstrøm et al 2021 ), and there is reason to hypothesise that experiencing restraint during dental treatment is a negative experience which can influence DFA. Painful dental treatment is one of the most frequently mentioned causes of DFA and BMP, especially in combination with a feeling of lack of control (Seligman et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Public Dental Service (PDS) in Hordaland, Norway, 17- and 9-year-old patients with self-reported history of restraint have significantly higher dental fear and anxiety (DFA) compared with patients without self-reported history of restraint (Aarvik et al 2022 ). The strong association between DFA and dental avoidance is well known (Armfield et al 2007 ; Fägerstad et al 2019 ; Skaret et al 1999 ), and the latter has negative consequences for oral health and higher total time use in the PDS (Skaret et al 1998 , 2000 ; Wang and Aspelund 2009 ; Åstrøm et al 2021 ). In 2009, Wang et al suggested that children who do not attend their scheduled dental appointments should be considered as risk patients and be offered customised dental care (Wang and Aspelund 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation